KONTRIBUSI MODEL INQUIRY TERBIMBING TERHADAP KEMAMPUAN PENALARAN MAHASISWA PROGRAM STUDI MANAJEMEN PADA MATA KULIAH MATEMATIKA EKONOMI - Irvan Malay (MES: Journal of Mathematics Education and Science, 2022)
The purpose of this study was to determine the contribution of the guided inquiry learning model to the reasoning ability of students. This research is a quasi-experimental study using two groups of samples (experimental and control) that have been declared normal and homogeneous. The study was conducted at SMP Negeri 27 Medan in 8th-grade students with two classes sample, each class with 40 students. The instrument used was in the form of a reasoning ability test consisting of pretest questions (6 items) and posttests (3 items) which have been declared valid and reliable. The results showed that in the guided inquiry class, students 'reasoning ability was influenced by the KAM value of 66%, while in the expository class, students' reasoning ability was influenced by the KAM value of 71.3%. This shows that the contribution of KAM in the guided inquiry class is smaller than the contribution of KAM in the expository class on reasoning ability (66% 71.3%).